2009
DOI: 10.1111/j.1567-1364.2009.00551.x
|View full text |Cite
|
Sign up to set email alerts
|

Complete mitochondrial genome sequences of  threeNakaseomycesspecies reveal invasion by palindromic GC clusters and considerable size expansion

Abstract: Here we report the sequence of three mitochondrial genomes from yeasts of the Nakaseomyces clade that includes the pathogenic yeast Candida glabrata, namely, that of Kluyveromyces delphensis, Candida castellii and Kluyveromyces bacillisporus. The gene content is equivalent to that of C. glabrata, but reveals the existence of new group I introns in COX1 and CYTB and new potential intronic endonucleases. Gene order is highly rearranged in these genomes, which contain numerous palindromic GC clusters. The more GC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 28 publications
2
25
1
Order By: Relevance
“…Comparative analysis across seven Lachancea species, concluded that ultimately, mt genome evolution is mostly related to intron motility and intergenic region variation. This finding was reported in other instances as well, both between closely and distantly related species (Bouchier et al 2009; Gaillardin et al 2012). …”
Section: Resultssupporting
confidence: 88%
“…Comparative analysis across seven Lachancea species, concluded that ultimately, mt genome evolution is mostly related to intron motility and intergenic region variation. This finding was reported in other instances as well, both between closely and distantly related species (Bouchier et al 2009; Gaillardin et al 2012). …”
Section: Resultssupporting
confidence: 88%
“…This size variation is correlated with either the relative size of intergenic sequences or the intron content (Table 1). By contrast to the genomes of the Nakaseomyces clade, we did not observe a relation between the number of GC clusters and the size of these genomes (data not shown) [23]. Intergenic regions range from 23.1% in L. mirantina to 58% in L. kluyveri .…”
Section: Resultscontrasting
confidence: 64%
“…The synteny varies considerably within Hemiascomycetes, which reflects small rearrangements occurring in the history of hemiascomycete fungi. As an example, gene order is highly rearranged in the mt genomes of yeasts of the Nakaseomyces clade [23]. Inversion as well as movement of short intergenic repeat and mobile introns seems to be at the origin of this variability [24].…”
Section: Resultsmentioning
confidence: 99%
“…In C. glabrata , the CGN-codon family has been entirely eliminated due to the loss of the cognate tRNA molecule (Koszul et al 2003). Considerable size variation of mtDNA molecules is also observed between related species, ranging from ∼20 kb in C. glabrata to almost 110 kb in Nakaseomyces bacillisporus (Bouchier et al 2009). Size variation is due in part to the presence/absence of group-I and group-II introns.…”
Section: What Did We Learn From Comparative Genomics Of Other Saccharmentioning
confidence: 99%
“…Size variation is due in part to the presence/absence of group-I and group-II introns. But it also results from the invasion of short GC-rich palindromic clusters of unclear origin associated with the expansion of large AT-rich intergenic regions (Bouchier et al 2009). These elements were discovered long ago in S. cerevisiae (Dujon 1981), but their patchy distribution across the entire phylogeny of Saccharomycotina species (Freel et al 2015) raises an interesting problem to examine.…”
Section: What Did We Learn From Comparative Genomics Of Other Saccharmentioning
confidence: 99%